2007
DOI: 10.1007/s11934-007-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for benign prostatic hyperplasia

Abstract: This review summarizes recent findings regarding risk factors for benign prostatic hyperplasia (BPH), including new data on hormonal factors, growth factors, comorbid conditions and lifestyle, diet, and exercise as they relate to BPH. In addition, it addresses the design and measurement issues that influence the inference that can be drawn from those studies. Most of the population-based studies on BPH have provided only modest insight into risk factors for BPH. The relationships with circulating levels of ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…13 Blacks and possibly Hispanics appear to be at increased risk of clinical BPH and surgery, whereas Asians are at a decreased risk when compared with whites. 12,15,16 Recently, diet and exercise have been associated with the development of BPH. 12,15,16 Recently, diet and exercise have been associated with the development of BPH.…”
Section: Known Risk Factors For the Development Of Bphmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Blacks and possibly Hispanics appear to be at increased risk of clinical BPH and surgery, whereas Asians are at a decreased risk when compared with whites. 12,15,16 Recently, diet and exercise have been associated with the development of BPH. 12,15,16 Recently, diet and exercise have been associated with the development of BPH.…”
Section: Known Risk Factors For the Development Of Bphmentioning
confidence: 99%
“…12,16,[50][51][52] Causal relationships have not yet been established for any of these. 12,16,[50][51][52] Causal relationships have not yet been established for any of these.…”
Section: Putati Ve Mechanisms For the Eff Ects Of Exercise On Bphmentioning
confidence: 99%
“…However, the etiology of BPH is not well understood. Some studies suggested that potential risk factors for BPH include diabetes, obesity, physical activity, alcohol consumption, dyslipidemia, hypertension, smoking, diet, and the environment (Parsons et al ., ; Jacobsen, ; Parsons, ). One recent meta‐analysis also concluded that the metabolic syndrome (MetS) construct is specifically associated with a greater overall prostate volume increment (Gacci et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…As a part of the aging process in men, the increase in the size of the prostate and the development of BPH is thought to be mediated by the effects of steroid hormones, particularly DHT (Carson and Rittmaster 2003) and estrogen (Sciarra and Toscano 2000) on the proliferation of prostate cells. Although the influence of androgens and estrogens has been demonstrated, hormonal factors alone may not fully explain the age-dependent morphological changes of prostate and pathogenesis of BPH (Lagiou et al 1997;Djavan et al 2002;Meigs et al 2002;Lee and Peehl 2004;Campbell 2005;Jacobsen 2007;Fibbi et al 2010;Ho and Habib 2011;Nicholson and Ricke 2011). The etiology of BPH is believed to be multifactorial.…”
mentioning
confidence: 99%